Pengaruh Coping, Dukungan Keluarga dan Motivasi terhadap Kualitas Hidup Pasien Kanker Serviks: The Influence of Coping, Family Support and Motivation on the Quality of Life of Cervical Cancer Patients - Sobar; Suhartini, Leni (MPI Press, 2022)
Introduction: Many women die because of cervical cancer. Treatment for cervical cancer is based on the stage of cancer. Such as radical hysterectomy, radiation, chemotherapy, and chemoradiation. Side effects of treatment can appear and make changes both physical and psychological. Objectives: The objective of this study is to determine the influence of coping, family support, and motivation on the quality of life in cervical cancer. Method: The method used in this study is cross-sectional, the transverse direction using a sample of 54 cervical cancer patients who get treatment (hysterectomy, radiation, chemotherapy, and chemoradiation) in Indonesia Army Hospital Gatot Soebroto 2015. Primary data was used in this study by questionnaire. Later in the analysis technique uses a quantitative approach, with analysis using Structural Equation Modeling (SEM), and using the SPSS application, and SmartPLS 2. Result: The result of this study, the family support variable can explain the coping variable 15,9%, and 84,1% is explained by another variable outside of this study. The family support variable can explain 39,2% quality of life of cervical cancer patients and 60,8% was explained by another variable outside of this research. The family support variable can explain 58,7% motivation variable and 41,3% was explained by another variable outside of this study Conclusion: The q square result analysis model can explain 78,9% phenomenon of this study, while 21,1% was explained by another component of this study.